O desenvolvimento do comércio eletrônico no âmbito internacional da Convenção Internacional de Compra e Venda de Viena - Silva, Luciana Vasco da (2016)
Internet development was responsible for the creation of an electronically internationalized and connected market, encompassing millions of companies and individuals, which benefit from the quick and practical contact provided by electronic means. In the beginning, the electronic contract was simple, however, with the increasing volume; complexity has become one of the e-commerce characteristics. Such contracts, of electronically partial or integral execution, have started to regulate the juridical relationship of parties situated in different states, due to Internet and globalization transnationality, resulting in electronic international contracts, object of the present study. Interested in delineating the main aspects of the subject of electronic international contracts in international scenario, some rules elaborated by states and International Organizations are analysed, seeking to ensure rights and obligations similar to those existing in material documents, in paper. After the described investigation, the study is concluded with the analysis of the most important law regarding the theme, passed in 2014: The United Nations Convention on Contracts for the International Sale of Goods, which even being innovative, does not mention the electronic contract, but can be easily adapted to this contracting fashion